New updates on yellow woodbrown Lethe nicetas Hewitson, 1863 from Rara National Park, Nepal - Suwal, Sanej Prasad (Nepalese Journal of Zoology, 2024)
This study presents new findings on the distribution and ecological characteristics of the yellow woodbrown Lethe nicetas butterfly in Rara National Park, Nepal. This butterfly species, which was previously only reported mainly from Eastern and Central Nepal, is recorded for the first time from the Western region of Nepal. The specimen was observed in October, and hence extends the seasonal range of observation of adults beyond the months of May-July. I have given a thorough description of L. nicetas, highlighting its characteristic patterns. The study reports the species' existence in the sub-alpine region, thereby extending its known habitat. I observed mud-puddling behavior of the specimen close to Rara Lake, which provided insight into its ecological preferences. The study's importance lies in the expansion of the butterfly's known distribution region and documenting its occurrence in a different Month for Nepal. The newly discovered data helps us comprehend the biological dynamics and habitat needs of various species. This study highlights the significance of continued butterfly species investigation and documentation in Nepal's varied landscapes and offers useful information for conservation initiatives.